Implementasi Project-Based Learning Pada Mata Pelajaran Instalasi Motor Listrik - Saputra, Ferdi Jansen; Hamdani, Hamdani (Jurnal Pendidikan Teknik Elektro, 2025)
Education plays an important role in the overall development of individual potential, as stipulated in the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. At the Vocational High School (SMK) level, education is oriented towards developing students' professional competencies following their fields. One of the subjects at SMK Negeri 2 Payakumbuh, especially in the Electrical Power Installation Engineering department, is Electric Motor Installation which involves theory and practice. However, observations show that learning tends to be passive, so students lack creativity and do not understand the material. This research aims to overcome these problems by applying the Project-Based Learning (PjBL) learning model. PjBL is an approach that involves students in designing and completing real projects, which aims to improve critical thinking skills, creativity, and collaboration. The method used in this research is a quantitative approach with a type of pre-experimental research, the pre-experimental research design used is One Shot Case Study. This design involves one group where the practicum value before the application of the Project-Based Learning model (O1), given treatment (X), and the practicum value after the application of the Project-Based Learning model (O2). The subjects of this study were students of class XI TITL 2 SMK Negeri 2 Payakumbuh in the 2024/2025 academic year